Approach to Pandemic 2009 influenza: first report from a main referral hospital for Pandemic H1N1 influenza care in Iran - Simin Dashti-Khavidaki; Hossein Khalili; Farid Gholamalipour; Abdolreza Soudbakhsh; Azita Hajhossein Talasaz; Mahboobeh Hajabdolbaghi; Mehrnaz Rasoolinejad; Talat Mokhtari Azad; Mehdi Fathi; Mohammad Taghi Talebian; Somayeh Nasiripour (Journal of Infection in Developing Countries)
Introduction: Pandemic H1N1 influenza A (pdmH1N1) was a major health threat worldwide.